Designing an Entrepreneurship Process Model in Coastal Tourism in Bushehr Province Using the Grounded Theory Approach - Zeinab Bahraini; Nader Naderi (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2020)
This research is attempting to adopt a non-teleological approach to the entrepreneurship process in the coastal tourism area of Bushehr province. The present study is theoretical and applied in terms of its objective. The research method is descriptive in terms of data collection method. Also, the present research is a qualitative research whose strategy is based on grounded theory. Considering experts of coastal tourism as the statistical population of the study, 9 people are selected as research experts using the purposeful sampling method. Then, the data are collected using semi-structured interviews and analyzed in three stages of open, pivotal and selective data coding.In the prescriptive process model of this research, the main phenomenon is the recognition and exploitation of the proper opportunity that is due to the characteristics and background of the entrepreneur